A duty of care to prevent online exploitation of consumers? Digital dominance and special responsibility in EU competition law. (16th August 2019) - Sauter, Wolf
Abstract: Article 102 Treaty on the Functioning of the European Union imposes a special responsibility on undertakings with a dominant position. Digital dominance based on data but also on network effects, platforms, and first user advantage can lead to extreme inequality in bargaining positions with regard to online services, which can result in unfair treatment of competitors, suppliers, and consumers—such as exploitation and discrimination. Online consumers are the focus of this article. In order to tackle competition issues regarding online consumers, I propose interpreting the special responsibility of digitally dominant undertakings as a duty of care in their regard. Digitally dominant undertakings may not just be burdened by but also benefit from this approach, which increases predictability and trust in online markets. It resembles treating online undertakings as information fiduciaries as has been proposed in the USA, but is different because privacy is not the driving concern here and the context is that of antitrust. I look at standards for triggering the duty of care and make proposals for the application of this norm, but both remain to be specified further.